Low or High-Level Motor Coding? The Role of Stimulus Complexity - Amoruso, Lucia; Finisguerra, Alessandra (Frontiers in Human Neuroscience, 2019)
Transcranial magnetic stimulation (TMS) studies have shown that observing an action induces activity in the onlooker’s motor system. In light of the muscle specificity and time-locked mirroring nature of the effect, this motor resonance has been traditionally viewed as an inner automatic replica of the observed movement. Notably, studies highlighting this aspect have classically considered movement in isolation (i.e., using non-realistic stimuli such as snapshots of hands detached from background). However, a few recent studies accounting the role of contextual cues, motivational states and social factors, have challenged this view by showing that motor resonance is not completely impervious to top-down modulations. A debate is still present. We reasoned that motor resonance reflects the inner replica of the observed movement only when its modulation is assessed during the observation of movements in isolation. Conversely, the presence of top-down modulations of motor resonance emerges when other high-level factors (i.e., contextual cues, past experience, social and motivational states) are taken into account. Here, we attempt to lay out current TMS studies assessing this issue and discuss the results in terms of their potential to favor the inner replica or the top-down modulation hypothesis. By doing so, we seek to shed light on this actual debate and suggest specific avenues for future research, highlighting the need for a more ecological approach when studying motor resonance phenomenon.